Situation, Risks and Prevention Strategies of Elder Abuse: A Lesson for Nepal - Nepal, Narayani; Aryal, Bhagwan; Poudel, Bhumidatta (Mangal Research Journal, 2023)
The purpose of this paper is to identify and summarize the body of research on elder abuse in order to offer a more thorough understanding of the topic. Specifically, the goal is to identify and discuss the situation, risks and preventive measures related to elder abuse in light of Nepal’s aging population. This narrative review was conducted after searching the article databases including Google Scholar, PubMed and Nepjol. A total of twenty seven journal articles, four systematic review articles, five books, five reports, one dissertation, two national acts of Nepal, four webpage articles and one methodological journal article were reviewed during a period from September 2022 to June 2023. The narrative review in the area of elder abuse is reflected in this article. Studies have shown that several misuse hazards are higher for senior citizens. Elder abuse is any single or recurrent act that hurts or distresses an older person and takes place in any relationship where there is an expectation of trust. The aging populations of many nations, including Nepal, are growing quickly, as are the number of senior abuse incidents. There are numerous government organizations, international and national non-governmental organizations, and local bodies doing admirable work concerning the investigation of elder abuse and the provision of assistance to elder abuse victims through the sharing of research experiences and the practical implementation of various prevention strategies. However, much more needs to be done for this at-risk population group in our society. In addition to raising social security for all seniors, it is recommended that each municipality in Nepal build an Elderly Service Center.